A systematic review of the parasites (Plathelminthes: Cestoda) of the domestic goose (Anser anser dom.) - Rzayev, F.; Nasirov, A.; Gasimov, E. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2021)
In many countries, poultry (including Anser anser dom.) play an important role in meeting population needs for meet. One of the factors that affect directly the meat quality and the industrial products obtained from domestic waterfowl are helminths, which cause diseases in their hosts. Helminthological research of the helminth fauna of domestic geese has been carried out in many countries, including Azerbaijan. Nevertherless, there is no general survey or species list of the world fauna of the domestic goose helminths. Tapeworms (Class: Cestoda) also parasitize the geese, causing them serious harm. Taking into account the relevance of the topic, we set the task to determine and systematize the species composition of tapeworms parasitizing the domestic goose (A. anser dom.) with the use of extensive literature data and our personal material. The species list is arranged in alphabetical order, families, genera and species of cestodes follow the nomenclature and classification by Khalil et al. (1994) and Olson et al. (2001), with updates by Kuchta et al. (2008) and Caira et al. (2014). We also took into account the classification adopted from the database of Fauna Europaea. Each species is provided with the following data: scientific name, author and year of description, synonyms, final, intermediate and auxiliary hosts, habitat in the bird body, collecting localities, geographic distribution, prevalence (PI) and intensity (II) of infection, and literature sources. An analysis of the worldwide literature and our personal data has established that 147 helminth species (Trematoda – 64 species, Cestoda – 33, Nematoda – 46, Acanthocephala – 4) are hitherto known from the domestic goose. The 33 tapeworm species of this list belong to five families (Dilepididae – 1 species, Hymenolepididae – 27, Mesocestoididae – 1, Paruterinidae – 1, and Diphyllobothriidae – 3). In Azerbaijan, 11 cestod species were found in the domestic goose. Six of them (Diorchis inflata, Drepanidotaenia lanceolata, D. przewalskii, Fimbriaria fasciolaris, Tschertkovilepis setigera, Ligula intestinalis) were registered in the course of our helminthological studies. The cestodes D. inflata and L. intestinalis were recorded in domestic geese in Azerbaijan for the first time. Five helminth species (Dilepis undula, Drepanidotaenia lanceolata, Ligula interrupta, L. intestinalis, Schistocephalus solidus) parasitize both birds and mammals (D. lanceolata in humans). Of these, two species (D. lanceolata and L. intestinalis) were found in Azerbaijan.